Phenotypic Plasticity and Functional Shift in Cisplatin-Resistant Cervical Cancer Cell Line - Kristiani, Lidya; Ivana, Kathy; Gabriela, Vania; Rattu, Shereen Angelina; Tanoto, Joselyn Phoebe Wylma; Dearyza, Sonya; Angelica, Rosemarie; Wirabuana, Shareena; Dreesa, Amelia; Tehubijuluw, Marcella Diviani; Crystalia, Audrey Amira (http://dharmais.co.id/, 2026)
Background: Cervical cancer remains the deadliest cancer among women. Furthermore, the development of resistance toward cisplatin, the golden standard treatment, has posed a significant challenge, threatening therapeutic efficacy and contributing to tumor recurrence. While enhanced DNA repair and drug inactivation have been implicated in resistance, their impact on cervical cancer remains poorly understood. This study aims to generate cisplatin-resistant cervical cancer cell lines to explore potential phenotypic and functional changes.Methods: We generated cisplatin-resistant cells through repeated exposure to increasing cisplatin concentrations up to 8 µM. Morphological changes were analysed using ImageJ software. Using manual hemocytometer counting, we generated a growth curve to assess cell growth, while a migration assay measured wound closure over time. Mitochondrial activity was evaluated using the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay, and gene expression of p53, Bax, and β-actin was quantified via qPCR. Statistical analysis, including two-tailed Student’s t-tests, was performed to compare wild-type and treated groups, with significance at p 0.005. Graphs and data visualization were performed using Microsoft Excel and GraphPad Prism 10.2.3.Results: Cisplatin-resistant (CPR) HeLa cells exhibited concentration-dependent morphological changes, including multinucleated